Conclusion, performance and termination of the contract in the law of Republic of South Africa - K M Belikova; V Y Ifraimov (RUDN Journal of Law, 2014)
The article touches upon the procedure of conclusion, performance and termination of the contract in the law of the Republic of South Africa. The authors distinguish the features of the development of contract law, as a result of the consideration of which come to the appropriate conclusions.